HOSPITAL HOME CARE SERVICE : PATIENT PERSPECTIVES AT A PRIVATE HOSPITAL IN BLITAR REGENCY - Fatmawati, Dwi Indah; Dewanto, Aryo (Universitas Brawijaya, 2025)
Hospital-based home care is an innovative service offered by hospitals, emerging as a crucial solution for patients requiring continued care at home. Hospitals inherently possess a significant potential to provide home care services due to the rising demand for these services, particularly because of the flexibility and convenience they offer. This study aims to explore patient and family perspectives on home care services and to identify the potential for developing such services in the private hospital where the research was conducted. A qualitative approach was employed through in-depth interviews with ten patients and their families-both inpatients and outpatients-at a private hospital in Blitar Regency. Thematic analysis was used to categorize interview results into emerging themes. Four primary themes were identified: patient and family understanding of home care services, types of services needed, expectations from the service, and perceived barriers. The findings also reveal the potential to develop home care services for both chronic and non-chronic patients based on specific needs. These results can be utilized by private hospitals as a foundation for home care service development, particularly focusing on chronic disease management and other medically indicated services.